Revisitando a curva de Phillips e a Regra de Taylor para a economia brasileira - Fernandes, Afonso Fonseca (2018)
This paper has two main objectives: to estimate a new basic Phillips curve for the Brazilian economy and the Taylor rule for Brazilian monetary policy. It is divided into two chapters: Chapter 1, entitled "Revisiting the Phillips Curve for Brazil," and Chapter 2, "Revisiting the Taylor Rule for Brazil." The period under investigation comprises from 2001: 12 to 2016: 05 and is characterized by the adoption of monetary regime of inflation targets by the Central Bank from 1999, for both objectives were used models through the OLS and GMM methods. For the first objective, we estimated the Phillips curve with the inclusion of variables not yet contemplated by the Brazilian economy, which are: compulsory deposit and public debt / GDP. The results show that the compulsory deposit variable had a low effect on inflation and could be used by the Brazilian Central Bank as an instrument of financial stability, but not as a price control instrument, and public debt / GDP was statistically insignificant in the models, indicating that the contracting or payment of public debt by the government was not an effective instrument to control inflation in the analyzed period. Regarding the second objective, the unpublished variable is real estate financing, and the result suggests that monetary policy acted procyclically at the activity level in the real estate sector during the analyzed period and the presence of expected inflation confirms forward-looking behavior adopted by economic agents in the same period.